Theoretical design of vascular imaging based on hall effect. Issue 1 (13th February 2013) - Pan, Junjun; Zhang, Jian J.
Abstract The conceptual technique of vascular imaging and blood flow functional imaging based on Hall Effect is presented in this article. With this non‐invasive approach, both 3D anatomical imaging of the vasculature and functional imaging of blood flow in the deep structure of the human body can be obtained without radiation risk. The technique is based on the fact that the induced charges can be generated when the blood flows through the magnetic field. The induced electric field strength is measured by two groups of detector arrays, which captures not only the position of vasculature in each section, but also the velocity of blood flow and vessel size. The captured images can also be used for 3D reconstruction of the anatomical models. The designed system architecture including both hardware and software is described. © 2013 Wiley Periodicals, Inc. Int J Imaging Syst Technol, 23, 85–96, 2013